Pengaruh Latihan Drilling Smash Sasaran Berubah Dan Drilling Smash Sasaran Tetap Terhadap Ketepatan Smash Atlet Bolavoli Putra Klub Nagamas Boyolali - Refi Mauliana Ulyasari; Agung Wahyudi; Tri Nurharsono; Dwi Gansar Santi Wijayanti (Indonesian Journal for Physical Education and Sport, 2024)
This study uses quantitative with an experimental method using Two Group Pretest-Postest Design by dividing into two groups and then doing pretest before and posttest after the administration of treatment. Precision instruments Smash Using the Precision Test Smash Instruments by Robet E. Laveage (Wibowo 2022). The population in this study is male football athletes aged 16-17 years old from the Nagamas Boyolali football club. The sampling technique is a total of 25 male athletes. Results after being given a workout drilling goals change and drilling The goal remains to experience an increase where the results pretest drilling target changed by 56.42 and posttest by 69.50 with an increase in results of 13.08%. While in the training drilling Fixed goal of results pretest by 56.58 and posttest by 64.50 with an increase in results of 7.92%. And the results were obtained there were significant differences Between Exercises drilling smash Fixed target as well as target varies (changes) to the accuracy of the shot Smash men's soccer athletes of the Nagamas Boyolali Club, with a t-count of 3.57 > a t-table of 2.07, and a significance value of 0.001 < 0.05